Withaferin A – A natural multifaceted therapeutic compound - Vinod, Sangeetha; Senthil, Kalaiselvi (Current Botany, 2021)
COVID 19, which has lead to the death of millions of people, is still spreading worldwide. The development of any new drug after proper trial is much time consuming. This present global pandemic situation has lead the researchers around the world to run behind various existing antiviral and immunomodulatory natural compounds to overcome this contagious disease. Withania somnifera (ashwagandha) that is being used in Ayurvedic medicine for several ailments since several years is also said to pocess anti viral activity. Thus many of its metabolites are being studied individually for its efficacy against the dreadful disease. Withaferin A, a steroidal lactone from ashwagandha is one such prime metabolite which beyond acting as an antioxidant or antimicrobial agent, is also said to pocess anti-inflammatory to anti carcinogenic properties. Thus because of its wide spectrum of medicinal properties it has now become an attractive drug candidate for several preclinical studies. This increase in the demand for withaferin A has chanelled its way towards in vitro propagation of the plant Withania somnifera and trials on various strategies to increase the yield in terms of plant biomass as well as the withaferin content in the plants thus making it a better alternative to field grown plants. Thus this article reviews in depth on the important medicinal properties of withaferin A, its demand in Ayurveda industry and the in vitro strategies being carried out to overcome the demand.